The subjective impact of the traumatic experience of clean-up workers of Chernobyl power plant accident 27 years after the disaster - Auškalnytė, Aurelija; Skruibis, Paulius; Povilaitienė, Ieva; Grigienė, Dovilė; Gailienė, Danutė (Psichologija, 2014)
A long-term psychological trauma is considered to be a possible consequence of being informed of radioactive contamination. In the case of the Chernobyl disaster, various circumstances possibly have led to even more serious psychological damage. For example, the socio-political context of the accident could be linked to extremely restricted information given out to the public. This disaster particularly affected clean-up workers, some of whom were brought from Lithuania, part of the Soviet Union at the time. This study thus is aimed to reveal the perceived impact of the traumatic experience of clean-up workers 27 years after the Chernobyl Disaster. Semi-structured 32 interviews with clean-up workers (age varying from 47 to 77 years), who are currently living in Lithuania, were conducted. A thematic analysis of the responses reveals that the clean-up workers are still feeling influenced by what they have experienced in Chernobyl. First of all, they link various health problems, which they are suffering from, to their presence in Chernobyl and express anxiety about the possible future illnesses, as they believe their bodies are irreversibly damaged by radiation. Secondly, the clean-up workers express a lot of anger towards the government for insufficiently supporting them financially and not showing enough gratitude for the work that they have done. Also, they experience a feeling of injustice as they believe that the government considers their experience in Chernobyl to be voluntary and not significantly influencing their present physical and psychological condition. Finally, post-traumatic stress symptoms were also found to be manifested. As the most distressing of those symptoms the clean-up workers name general irritability and anxiousness, although symptoms of intrusion and avoidance can also be detected as well as helplessness and a feeling of constantly living under threat. All these findings raise the awarness of how important it is that the government and society would validate the clean-up workers’ experiences – at least symbolically recognizing the long-term impact of being in Chernobyl as well as its involuntary nature. This recognition should also lead to the necessary physical and psychological help in consideration of the clean-up workers’ traumatic experiences and the psychological component of their physical illnesses.
Keywords: Chernobyl accident; clean-up workers; psychological impact of exposure to radiotion; psychological trauma; health related stress